(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This empirical study ventured to compare the aerobic capacityof handball and basketballplayers hailing from LNIPE, NERCE, Guwahati, Assam. In total, 30 subjects participated, evenly split with15 individuals representing each sport. Aerobic capacity serves as a crucial determinant in assessing anathlete’s capability to sustain prolonged physical activity, which is critical in high-intensity sports such ashandball and basketball. Utilizing the Yo-YoIR1test, a widely acknowledged method for measuring aerobiccapacity, the study aimed to discern any significant disparities in Aerobic capacity between the twogroups of players. The findings indicated a notable superiority in aerobic capacity among handballplayers compared to their basketball counterparts. This difference accentuates the necessity for sportspecificconditioning and training programs to optimize the athletic prowess and performance in diversesporting disciplines. t-test statistical analysis was utilized, with a 0.05 level of significance.